The Military Surgery in Uruguay from the lndependence to the Paraguay War - Bergalli, Luis (Cirugía del Uruguay, 1980)
The history of Uruguay in the past century was rich in military events. After the Independence War, the ones against Brazil and Argentine succeded and culminated at the Guerra Grande and finaliy with the Triple Alliance Campaign against Paraguay. The author tells the history of military surgery in this turbulent century ponting out the outstanding figure of Spielman among Artigas surgeons and Fermín Ferreira in the Guerra Grande and Paraguay's War. A comparison is made between these River Plate's wars and tho·se that simultaneously took place in Europe and North America: Crimea, Prussian and Civil War.